The relationship between transformational leadership behaviors, organizational justice, leader-member exchange, perceived organizational support, trust in management and organizational citizenship behaviors - Asgari, Ali; Silong, Abu Daud; Ahmad, Aminah; Abu Samah, Bahaman (EuroJournals Publishing, 2008)
The current study explored the relationship between transformational leadership behaviors, and organizational justice and organizational citizenship behavior (OCB), that mediated by LMX, POS and Trust. Survey data was collected from a sample of 162 employees in five ministries in Putra Jaya city of Malaysia. The results of structural equation modeling showed that the hypothesized model fit the data very well. There are positive and direct relationship between transformational leadership behaviors (transformational and transactional), and organizational justice (distributive, procedural, and interactional justice) and OCB with leader-member exchange (LMX), perceived organizational support (POS), and Trust as the mediators.